Effects of Participation in Online Quizzes and Pre-Examination Engagement on Academic Performance in Demography: A Study of University Students in a Non-Mandatory Attendance Setting - Pewnil, Titinan (Journal of Research Methodology, 2025)
This study examines the effects of online quizzes and pre-examination engagement on academic performance in demography among university students in a non-mandatory attendance setting. The sample consisted of 43 enrolled students who took the final examination, divided into an experimental group of 22 students who participated in quizzes and/or pre-examination activities and a control group of 21 non-participating students. Data were gathered through 10 quizzes, a pre-examination test, a satisfaction questionnaire, and the final examination. Results showed that students who participated in both activities achieved the highest academic performance (M = 82.20, SD = 9.60), followed by those who participated only in quizzes (M = 78.75, SD = 12.86). Activity participation was the most significant factor affecting academic achievement (β = .871). Students reported the highest level of satisfaction in all aspects, particularly in learning development assessment. These findings suggest that formative assessment through online quizzes and pre-examination activities effectively improves academic achievement among students in non-mandatory attendance settings.